Perlindungan Hukum terhadap Perangkat Desa yang Diberhentikan Tidak Sesuai dengan Peraturan Perundang-Undangan - Firdaus Hasanah; Syahrul Ibad; Dairani Dairani (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Village Apparatus is an element in the implementation of the Village Government to assist the head, the Village to carry out the duties and administration of the government, and the authority of the Village Head and village development, then in the Village the village apparatus is formed. The problem studied in this thesis is the process of dismissal of village apparatus carried out by village heads who do not follow the procedures that have been stipulated in the laws and regulations and regulations of the Minister of Home Affairs which have been clearly regulated the procedures and mechanisms for dismissing village apparatus. This skiffy research uses a qualitative approach or is often referred to as field research or uses the type of empirical research. From the results of the study, it was found that the village head dismissed his village apparatus not in accordance with the procedures and mechanisms in the laws and regulations and regulations of the Minister of Home Affairs, as evidenced by the results of research at the research location and interviews conducted with the head of the The village head, the dismissed village apparatus and the local community, the implementation of the dismissal of the village apparatus is considered irresponsible by the village head and the occurrence of the unilateral dismissal of the village apparatus, legal protection is needed for the village apparatus that is terminated not in accordance with the law, namely administrative legal protection and preventive and repressive legal protection, such as the lawsuit of the Sumber Kemuning village apparatus against the decision of the head The village for its dismissal as a village apparatus has been submitted to the Surabaya State Administrative Court and has been stipulated in decision Number 42/G/2022/PTUN. SBY, has prosecuted the village head by granting the village apparatus' claim in its entirety, declaring null and void the Decree of the Sumber Kemuning village head No. 188.4/12/430.11.2.8/2022 concerning the dismissal of the Sumber Kemuning village apparatus,